Fostering Climate Action Now and on Scale: Lessons from the DA-AMIA Program in the Philippines - Enriquez, A.; Cabriole, Marie Aislinn; Baltazar, P.; Ilaga, Alicia; Valenzuela, M. A.; Calvar-Adarayan, J.; Rosimo, Magnolia; Monville-Oro, Emily; Gonsalves, Julian (CGIAR System Organization, 2024)
This policy brief is based on the outcomes of a synthesis workshop on climate-resilient efforts in the Philippines, co-organized by the International Institute of Rural Reconstruction (IIRR) and the Department of Agriculture (DA) Climate Resilient Agriculture Office (CRAO), with support from the CGIAR Initiative on Climate Resilience. The Adaptation and Mitigation Initiative in Agriculture (AMIA) Program, led by DA-CRAO, has entered its third phase after ten years of successful implementation, securing buy-in and modest investments from regional offices across the Philippines. With its current regional scale, this brief advocates for nationwide expansion of the AMIA program across all provinces, leveraging its success to further enhance climate resilience in agriculture.